Tachycardia-induced cardiomyopathy in three consecutive pregnancies. (December 2021) - Pfaller, Birgit; Wichert-Schmitt, B; Spears, Danna; D'Souza, Rohan; Silversides, Candice K
Tachycardia-induced cardiomyopathy is rare during pregnancy and is reversible when the underlying arrhythmia is effectively treated. Management can be complex due to the risks of antiarrhythmic medications and cardiac interventions on the developing fetus. The care requires a well-coordinated multidisciplinary team of cardiologists, electrophysiologists, and maternal-fetal specialists. In this report, we describe a case of recurrent atrial tachycardia-induced cardiomyopathy in pregnancy.